Education of Love Your Body for Prevention of Sexual Behavior in Children Age at SDN 20 Kurao Pagang - Kontesa, Meria; Nurleny, Nurleny (Jurnal Peduli Masyarakat, 2020)
The problem of sex is still considered taboo among the people and is discussed in front of children let alone to teach it to children. Society thinks that sex education is not appropriate to be given to young children. Though sex education provided from an early age is very influential in a child's life when he enters adolescence. This problem of sex is not given enough attention by parents so they submit all children's education to schools including sex education. To face its future, knowledge and information about sex is very important to be known by the next generation. However, children and adolescents are vulnerable to misinformation about sex knowledge. If you do not get a proper sex education, they will believe in myths about sex that is not true. In addition, by providing sex education can prevent school-age children from occurring sexual behavior. Community service is carried out with education education methods for school-age children by using audio visuals such as watching movies and playing roles. The results obtained from increased knowledge of sexual behavior prevention in school-age children and participants are not shy to ask. So it can be concluded education education for the prevention of sexual behavior has a positive impact on school-age children.